2014
DOI: 10.1097/mao.0000000000000622
|View full text |Cite
|
Sign up to set email alerts
|

Altered Autonomic Regulation as a Cardiovascular Risk Marker for Patients With Sudden Sensorineural Hearing Loss

Abstract: ISSHL patients show an altered autonomic regulation. At least a subgroup of ISSHL patients seems to exist where a vascular impairment might play an important role in the pathogenesis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…It is also known that there is a relationship between different cardiovascular pathologies and SSNHL 21 . In a case-controlled study, it was found that the incidence of SSNHL was higher in individuals of families with cardiovascular events compared to the individuals of families with no cardiovascular events 22 .…”
Section: Discussionmentioning
confidence: 97%
“…It is also known that there is a relationship between different cardiovascular pathologies and SSNHL 21 . In a case-controlled study, it was found that the incidence of SSNHL was higher in individuals of families with cardiovascular events compared to the individuals of families with no cardiovascular events 22 .…”
Section: Discussionmentioning
confidence: 97%
“…The segmented short-term symbolic dynamics (SSD) was introduced in order to describe nonlinear aspects within longterm RR time series applying a 24-hour segmentation algorithm in an enhanced way [45,69]. Therefore, the related time series were segmented in both 1 min overlapping and non-overlapping time windows of 15 min, 30 min or 60 min duration.…”
Section: Symbolic Dynamicsmentioning
confidence: 99%
“…LZ77 was modified by Baumert et al in 2004 [37] to analysis heart rate time series called the compression entropy (H c ). in the field of spontaneous fluctuations of cardiovascular oscillations entropy based methods were applied to investigate fetal development [38], to determine age effects on the autonomic system [39][40][41], in differentiating pathological states from healthy states [42][43][44][45][46], for monitoring cardiac autonomic function [34,47], in typifying the effects of a pharmacological treatment [48][49][50][51], and in predicting risk [37,52].…”
Section: Introductionmentioning
confidence: 99%
“…In der Arbeit finden sich dazu aber keine näheren Ausführungen, insbesondere nicht, wie die "Hörschärfe" gemessen wurde. Eine Arbeit aus Jena will anhand von Daten bei 23 Hörsturzpatienten (verglichen mit 10 Normalhörenden) bei den Patienten eine veränderte autonome Kreislaufregulation gefunden haben[24]. Erfasst wurde die Kreislaufregulation mit einem EKG, das in Beziehung gesetzt wurde zu kontinuierlichen Blutdruckmessungen; erfasst wurde so die Kombination und Kopplung verschiedener kardiovaskulärer Faktoren, die sehr aufwändig statistisch ausgewertet wurde.…”
unclassified